FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA PASIEN PENYAKIT GAGAL GINJAL KRONIK DI RUANG HEMODIALISA RSUD PROF. DR. H. ALOEI SABOE KOTA GORONTALO - Ani Retni; Asni Ayuba (-, 2021)
The aims of this research is to determine the factors relevancy with the anemia incidence toward chronic renal failure patients undergoing hemodialysis routine. This research used analytic observational design with cross sectional approach. Total of the sample are 30 patients who underwent hemodialysis routine at Hemodialysis room of Prof. Dr.H.Aloei Saboe Hospital, Gorontalo. Analysis of the data is used statistical Chi-square test. The result of research showed there was no correlation between age and the anemia incidence toward CRF patients undergoing hemodialysis routine (P value 0,517), there was relevancy between nutritional status and the anemia incidence toward CRF patients undergoing hemodialysis routine (P value 0,001) and relevancy between time span of CRF patients undergoing hemodialysis routine with anemia (P value 0,000)